Poly(o-phenylenediamine) modified graphene toward the reinforcement in corrosion protection of epoxy coatings. (October 2019) - Cui, Mingjun; Ren, Siming; Pu, Jibin; Wang, Yonggang; Zhao, Haichao; Wang, Liping
Highlights: Poly(o-phenylenediamine) are used to disperse graphene nanosheets in order to improve the compatibility between graphene and epoxy matrix. The impedance modulus of 0.5∼1.0% G-Popd/EP is about 10 10 Ω cm 2 during 60 days of immersion. The corrosion of the substrate is retarded even if there is an artificial scratch to the G-Popd/EP. Abstract: In this research, soluble poly(o-phenylenediamine) nanoparticles were synthesized to noncovalently functionalize the graphene nanosheets via π-π interactions, and the corresponding protective performance of epoxy composite coatings was also investigated. Results showed that the impedance modulus of the composite coatings incorporated with 0.5–1.0% G-Popd was about 10 10 Ω cm 2 after 60 days of immersion. Furthermore, the corrosion of substrate was still retarded even if there is an artiﬁcial scratch to the composite coatings. The superior protective performance of the composite coating derived from the synergistic action in the barrier property of graphene nanosheets and metal surface passivation by Popd nanoparticles.